Perfectionism and Identity Processes in Two Domains: Mediational Roles of Worry, Rumination, Indecisiveness, Shame, and Guilt - Piotrowski, Konrad (Frontiers in Psychology, 2019)
The objective of the study was to assess the relationships between two dimensions of perfectionism, that is, perfectionistic strivings and perfectionistic concerns, and identity processes in the domains of future plans and education. It was hypothesized that such consequences of perfectionism as worry, rumination, indecisiveness, and guilt and shame proneness would be mediators of the perfectionism–identity relationship. A total of 696 students took part in the study (Mage = 26.74, SD = 7.56). It was found that perfectionistic strivings may promote the development of identity by supporting adaptive exploration and identity commitment. This relationship was only partly mediated. On the other hand, perfectionistic concerns were associated with significant difficulties with identity formation. This relationship was largely indirect, and indecisiveness proved to be the main mediator of the perfectionistic concerns–identity relationship. High indecisiveness, which disturbs decision-making processes, seems to explain why maladaptive perfectionists have problems with identity formation. These mediational effect was observed in both analyzed domains.